2021
DOI: 10.1007/s40744-021-00368-y
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Burden of Lupus Nephritis: A Systematic Literature Review

Abstract: Introduction Few studies have evaluated the economic burden of lupus nephritis (LN). The aim of this systematic literature review (SLR) was to assess the economic burden (direct and indirect costs, and healthcare resource utilization [HCRU]) associated with LN, with particular focus on the burden of renal flares and end-stage kidney disease (ESKD). Methods This SLR (GSK study 213531) was conducted and reported according to the Preferred Reporting Items for Systematic Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 60 publications
1
12
0
1
Order By: Relevance
“…Supporting the ndings of the current study, previous studies have reported increased HCRU and healthcare costs in patients with SLE with LN compared with patients without LN or matched controls [22][23][24][25][26][27]. Furthermore, Clarke et al compared annual direct medical costs of patients with varying degrees of renal damage and demonstrated that costs elevated with increasing degrees of renal damage [32].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Supporting the ndings of the current study, previous studies have reported increased HCRU and healthcare costs in patients with SLE with LN compared with patients without LN or matched controls [22][23][24][25][26][27]. Furthermore, Clarke et al compared annual direct medical costs of patients with varying degrees of renal damage and demonstrated that costs elevated with increasing degrees of renal damage [32].…”
Section: Discussionsupporting
confidence: 82%
“…3). This difference was mainly driven by the cost of inpatient admissions, for which the mean (SD) costs were $21,181 (58,886) in Year 1 and lower in subsequent years (Year 2: $7,406 [23,331]; Year 3: $8,197 [24,110]; Year 4: $8,555 [27,403]…”
Section: Sle Aresmentioning
confidence: 99%
See 1 more Smart Citation
“…3,5 Despite this, SLRs reporting the impact of LN on HRQoL, fatigue, and health utilities are limited. Although some SLRs have focused on the management and economic burden of LN, [44][45][46][47] there is a need for more SLRs that are focused on the humanistic burden. Therefore, this SLR was carried out to assess the impact of LN on HRQoL, fatigue, and health utilities in this specific subpopulation of patients with SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Несвоевременная диагностика и неадекватная терапия ВН являются факторами риска развития терминальной стадии почечной недостаточности и смерти [3,4]. Вместе с тем развитие ВН сопряжено со значительно более высокими прямыми и косвенными финансовыми затратами, чем СКВ без поражения почек [5]. ВН наблюдается при остром течении СКВ, чаще у пациентов с дебютом заболевания в детском и/или подростковом возрасте.…”
unclassified